Quinolone antibiotic sample pretreatment method and analysis application
By preparing cationic conjugated microporous polymer (CMP-I) as adsorption material, solid-phase extraction-liquid chromatography-tandem mass spectrometry (SPE-LC-MS/MS) analysis method was constructed, and the problems of difficulty in detecting residues of quinolones and low efficiency of adsorbent materials in the prior art were solved, and the detection effect of high sensitivity and low detection limit was achieved.
Patent Information
- Application Number
- CN202411812146.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
When detecting the residues of quinolones, the prior art has problems such as difficult pretreatment of samples and obvious influence of interfering components, and lacks efficient adsorbent materials to improve enrichment efficiency.
Conjugated microporous polymer (CMP) was prepared by Sonogashira Hagihara cross-coupling reaction, and methylated to obtain cationic conjugated microporous polymer (CMP-I). Using it as an adsorption material, solid-phase extraction-liquid chromatography-tandem mass spectrometry (SPE-LC-MS/MS) analysis method was constructed for the detection of quinolones antibiotics.
QA detection with high sensitivity and low detection limit is achieved, which can meet the detection needs of trace QA in meat and water, and significantly improve the efficiency and effect of sample pretreatment.
Smart Images

Figure CN119633783A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of solid phase microextraction devices, and specifically relates to a quinolone antibiotic sample pretreatment method and analytical application. Background Art
[0002] Quinolone antibiotics (QA) are an important class of synthetic antimicrobial agents. Due to their broad antimicrobial activity, lack of cross-resistance with other antimicrobial agents, and low toxic side effects, QA are widely used in disease prevention and control in animal husbandry, aquaculture, and related industries. However, the widespread use of QA and its inherent persistence have led to its residues in a variety of environmental and food matrices. A large number of studies have shown that the presence of QA can be detected in environmental water samples such as seawater, lake water, surface water, wastewater, and drinking water. Elevated levels of QA residues may pose a serious threat to health, affecting the digestive system and central nervous system, causing cartilage and joint damage, liver and kidney dysfunction, and may affect children's growth and development after long-term ingestion. In addition, QA can selectively eliminate or inhibit microorganisms, induce toxic reactions in aquatic organisms, and promote the evolution of antibiotic-resistant bacteria, thereby causing significant negative impacts on ecosystems and human health. Therefore, the National Food Safety Standard (GB 31650.1-2022) stipulates the maximum residue limits of veterinary drugs in 41 foods: 2 μg kg for norfloxacin and ofloxacin -1 , enrofloxacin is 10 μg kg -1 In order to further enhance the protection of ecosystems and human health, it is urgent to develop an effective analytical method for detecting QA residues.
[0003] At present, the generally recognized QA detection methods in the prior art include gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry. In particular, liquid chromatography-mass spectrometry is widely used due to its excellent sensitivity. Given that the matrices of environmental and food samples are usually complex, it is difficult to directly detect the QA components therein. Therefore, it becomes necessary to pre-treat the samples in order to concentrate the target substances and minimize the influence of interfering components. Common sample pre-treatment techniques include liquid-liquid extraction, solid phase extraction, and dispersed solid phase extraction. Among these methods, solid phase extraction has become one of the most popular techniques in QA sample pre-treatment because of its advantages of combining enrichment and purification, supporting automated batch processing, high detection sensitivity, rapid extraction, low solvent consumption, and good repeatability. In the solid phase extraction process, the adsorption material plays a decisive role in the enrichment efficiency of the target.
[0004] In recent years, the rapid development of porous organic polymers such as covalent organic frameworks (COFs) and metal organic frameworks (MOFs) has significantly promoted the development of adsorbents. Despite this, the development of adsorbent materials with specific functionalization to further improve the enrichment efficiency and reproducibility of materials is still a necessary and challenging task. Conjugated microporous polymers (CMPs) are a class of covalent organic porous materials that use π-electron conjugated delocalized skeletons. Due to their high specific surface area, rich pore structure, adjustable skeleton structure, and excellent chemical and thermal stability, this material has been widely used in many fields such as electrochemistry, adsorption, catalysis, and optics, and has shown great potential and practical application value.
[0005] Wang et al. developed a highly efficient cationic conjugated microporous polymer (CMP-Im) and studied its adsorption performance for anionic dyes. Wu et al. successfully prepared CMP / TiO2 nanocomposites, which showed excellent photocatalytic degradation of organic pollutants such as methylene blue, ciprofloxacin and tetracycline under visible light irradiation, with a degradation rate of more than 96.8%. Zang et al. synthesized a superhydrophobic CMP sponge coating (CMP@sponge) using silyl- and amine-containing monomers in the presence of melamine sponge through in situ Sonogashira coupling reaction. The material showed amazing absorption capacity for various oils and could absorb more than 80 times its own weight of oil. As an emerging organic porous material, ionic CMP has the key physicochemical properties required as a solid phase extraction adsorbent. Despite this, the application research of this type of material in the field of sample pretreatment is relatively small, and further in-depth exploration is urgently needed. Summary of the invention
[0006] The present invention aims to provide a quinolone antibiotic sample pretreatment method and analytical application to solve the defects of the prior art. By adopting the SonogashiraHagihara cross-coupling reaction, a conjugated microporous polymer (CMP) was successfully prepared, and the CMP was further methylated to obtain a cationic conjugated microporous polymer (CMP-I). Using CMP-I as the adsorption material, an analytical method based on solid phase extraction-liquid chromatography-tandem mass spectrometry (SPE-LC-MS / MS) was constructed for the detection and analysis of QA. This method shows high sensitivity and low detection limit, which can meet the detection needs of trace QA in meat and water.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] In a first aspect, the present invention provides a cationic conjugated microporous polymer, wherein the cationic conjugated microporous polymer is a methylated conjugated microporous polymer, and the conjugated microporous polymer is polymerized from two monomers: 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,5-dibromopyrimidine.
[0009] In a second aspect, the present invention provides a method for preparing the cationic conjugated microporous polymer according to the first aspect, comprising the following steps:
[0010] (1) After mixing 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, 2,5-dibromopyrimidine and a catalyst, the mixture is added into a solvent for cross-coupling reaction to obtain a conjugated microporous polymer;
[0011] (2) Adding a halogenated hydrocarbon solution to methylate the conjugated microporous polymer to obtain a cationic conjugated microporous polymer.
[0012] In some embodiments, in step (1), the molar ratio of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, 2,5-dibromopyrimidine and catalyst is 1:(1-3):(1-2);
[0013] Preferably, the molar ratio of the 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, 2,5-dibromopyrimidine and the catalyst is 1:1.5:1.3.
[0014] In some embodiments, in step (1), the catalyst is bistriphenylphosphine palladium dichloride, cuprous iodide and triphenylphosphine;
[0015] The molar ratio of bistriphenylphosphine palladium dichloride, cuprous iodide and triphenylphosphine is 1:(3-6):(1-3);
[0016] Preferably, the molar ratio of bistriphenylphosphine palladium dichloride, cuprous iodide and triphenylphosphine is 1:5.4:2.3;
[0017] Or, the solvent is triethylamine and N,N'-dimethylformamide; the volume ratio of triethylamine to N,N'-dimethylformamide is 1:(1-3);
[0018] Preferably, the volume ratio of triethylamine to N,N'-dimethylformamide is 1:1.
[0019] In some embodiments, in step (1), the conditions of the cross-coupling reaction are: stirring at 80-100° C. for 10-12 h under an inert atmosphere, and then refluxing at 110-150° C. for 60-80 h;
[0020] Preferably, the conditions of the cross-coupling reaction are: stirring at 90° C. for 12 h under nitrogen, and then refluxing at 120° C. for 72 h.
[0021] In some embodiments, in step (2), the mixing ratio of the conjugated microporous polymer to the halogenated hydrocarbon is (40-60) mg: 1 mL;
[0022] Preferably, the mixing ratio of the conjugated microporous polymer to the halogenated hydrocarbon is 50 mg: 1 mL;
[0023] The halogenated hydrocarbon solution is an acetonitrile solution of halogenated hydrocarbon; the volume fraction of the halogenated hydrocarbon is 0.1-0.2%;
[0024] The halogenated hydrocarbons are methyl iodide and methyl bromide;
[0025] Preferably, the halogenated hydrocarbon is methyl iodide;
[0026] The conditions of the methylation reaction are: stirring the reaction at 60-80° C. for 30-40 hours;
[0027] Preferably, the methylation reaction is carried out under stirring at 80° C. for 36 hours.
[0028] In a third aspect, the present invention provides the use of the cationic conjugated microporous polymer described in the first aspect as a solid phase extraction adsorbent in enriching quinolone antibiotics, wherein the quinolone antibiotics are norfloxacin, ciprofloxacin, enrofloxacin, gatifloxacin and ofloxacin.
[0029] In a fourth aspect, the present invention provides a method for enriching quinolone antibiotics, wherein the cationic conjugated microporous polymer described in the first aspect is fixed in a solid phase extraction column of a solid phase extraction device, solid phase extraction is performed to enrich the quinolone antibiotic residues in the sample, and the quinolone antibiotics in the sample are quantitatively analyzed by liquid chromatography-tandem mass spectrometry.
[0030] In some embodiments, during the solid phase extraction, the pH of the sample is 2-10; preferably, the pH of the sample is 2-4;
[0031] The amount of the cationic conjugated microporous polymer added is 20-60 mg; preferably, the amount of the cationic conjugated microporous polymer added is 40 mg;
[0032] Sampling flow rate is 1-5mL·min -1 ; Preferably, the sampling flow rate is 5mL·min -1 ;
[0033] The sample volume is 100-500 mL; preferably, the sample volume is 500 mL;
[0034] The eluent is ethyl acetate, 2,3-hexanedione, acetone, dichloromethane and methanol; preferably, the eluent is methanol;
[0035] The volume of the eluent is 2-10 mL; preferably, the volume of the eluent is 8 mL.
[0036] In some embodiments, the conditions for the liquid chromatography analysis are: the chromatographic column used is a BEH C18 chromatographic column, the injection volume is 1-5 μL, and the flow rate is 0.1-0.5 mL·min -1 , the column temperature is 30-35°C; the mobile phases used include phase A and phase B, the phase A is 0.1% formic acid aqueous solution, the phase B is pure acetonitrile, and gradient elution is used;
[0037] The procedure of the gradient elution is:
[0038] 0 min, mobile phase A was 87.5%, mobile phase B was 12.5%;
[0039] At 0-5 min, mobile phase A was reduced from 87.5% to 40%, and mobile phase B was increased from 12.5% to 60%;
[0040] At 5-5.1 min, mobile phase A increased from 40% to 87.5%, and mobile phase B decreased from 60% to 12.5%;
[0041] At 5.1-8 min, mobile phase A was 87.5% and mobile phase B was 12.5%;
[0042] Preferably, the BEH C18 column is 100 mm x 2.1 mm, 2.5 μm; the injection volume is 3 μL, and the flow rate is 0.3 mL min -1 , column temperature was 35°C;
[0043] Alternatively, the conditions for the mass spectrometry analysis are: ion source: electrospray ionization in positive ion mode; scanning mode: multiple reaction monitoring mode; ion source temperature is 500°C.
[0044] Beneficial effects of the present invention:
[0045] (1) The present invention utilizes the Sonogashira-Hagihara cross-coupling reaction to prepare a conjugated microporous polymer CMP, and uses CH3I to methylate CMP to prepare a cationic conjugated microporous polymer CMP-I. This preparation method has the advantages of simple synthesis and good reusability.
[0046] (2) The CMP-I structure prepared in the present invention is rich in triazine skeletons and pyrimidine rings, which enhances the ability of CMP-I to establish stronger cation-π and π-π interactions with QA molecules, thereby promoting the enrichment and detection of QA by CMP-I.
[0047] (3) The solid phase extraction-liquid chromatography-tandem mass spectrometry analysis method established by the present invention based on this CMP-I has high sensitivity and low detection limit, and can meet the determination requirements of trace QA in meat and water. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0049] Figure 1 The figures are scanning electron microscope images and transmission electron microscope images in the embodiments of the present invention, wherein (a) is a scanning electron microscope image of CMP, (b) is a scanning electron microscope image of CMP-I, (c) is a transmission electron microscope image of CMP, and (d) is a transmission electron microscope image of CMP-I;
[0050] Figure 2 Figure 1 is a material characterization diagram of the embodiment of the present invention, wherein (a) Fourier transform infrared spectrum, (b) solid-state CMP and CMP-I 13 C NMR spectrum, (c) N2 adsorption-desorption isotherm, (d) thermogravimetric analysis;
[0051] Figure 3 is the selection of adsorption materials in the embodiments of the present invention, wherein (a) the extraction efficiency of CMP, (b) the extraction efficiency of CMP-I, wherein EAC is ethyl acetate, ACN is acetonitrile, ACE is acetone, DCM is dichloromethane, and MA is methanol;
[0052] Figure 4 are parameters that affect the performance of CMP-I fillers in the embodiments of the present invention, including (a) sample pH, (b) adsorbent dosage, (c) sample flow rate, (d) sample volume, (e) ionic strength, and (f) eluent volume;
[0053] Figure 5 1 are the fitting model curves and models in the embodiments of the present invention; wherein (a) is a pseudo-first-order model curve, (b) is a pseudo-second-order model curve, (c) is a Langmuir model, and (d) is a Freundlich model;
[0054] Figure 6 The inter-column and intra-column cyclic test results of CMP-I on QA in the inventive example correspond to inter-column (a) and intra-column (b), respectively;
[0055] Figure 7 Schematic diagram of the synthesis process of CMP-I in the embodiment of the present invention and its application in the detection of quinolone antibiotics;
[0056] in, Figure 3-Figure 6 In the table, ENRO stands for norfloxacin, GAT stands for ciprofloxacin, CIP stands for enrofloxacin, NOR stands for gatifloxacin, and OFL stands for ofloxacin. DETAILED DESCRIPTION
[0057] Example 1
[0058] 1. Synthesis of CMP-I
[0059] (1) CMP synthesis
[0060] CMP is synthesized by Sonogashira-Hagihara cross-coupling reaction. The specific synthesis process is as follows:
[0061] 2,4,6-tri(4-ethynylphenyl)-1,3,5-triazine (TEPT, 2.28 g, 6.00 mmol), 2,5-dibromopyrimidine (DPDE, 2.1 g, 9.00 mmol), bis(triphenylphosphine)palladium dichloride Pd(PPh3)2Cl2 (0.61 g, 0.87 mmol), CuI (0.90 g, 4.73 mmol) and triphenylphosphine PPh3 (0.52 g, 1.98 mmol) were mixed and added to 60.0 mL of a solution containing triethylamine and N,N'-dimethylformamide in a volume ratio of 1:1 to obtain a reaction mixture.
[0062] Under nitrogen protection, the reaction mixture was vigorously stirred at 90°C for 12h, and then refluxed at 120°C for 72h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged and washed with tetrahydrofuran, chloroform, acetone and methanol to purify the obtained product. The purified CMP was placed in a vacuum oven at 80°C and dried for 12h to finally obtain brown powder CMP (3.3g, yield 75.3%).
[0063] (2) CMP-I Synthesis
[0064] 250 mg of the prepared CMP was added to 35 mL of a mixed solution of iodomethane and acetonitrile (volume ratio 1:6), and stirred vigorously at 80°C for 36 h. After cooling to room temperature, the solution was centrifuged and washed with chloroform, and then vacuum dried at 80°C for 12 h, finally obtaining CMP-I (340 mg) as a yellow-brown powder.
[0065] 2. Liquid chromatography UV detection conditions
[0066] The adsorption performance of CMP-I was tested by liquid chromatography, and the specific testing conditions were as follows:
[0067] HPLC-DAD equipment: Ultimate 3000 liquid chromatograph connected in series with a diode array detector. Liquid chromatography operating conditions: 0.1% phosphoric acid aqueous solution (pH = 3, adjusted with triethylamine) and methanol were used as mobile phases to chromatographically separate QA on a Unitary C18 column (150 mm x 2.1 mm, 5.0 μm); isocratic elution conditions were as follows: 0-20 min, 30% methanol; detection wavelength: 290 nm; flow rate set at 1.0 mL min -1 ; The injection volume was 10 μL.
[0068] 3. Liquid chromatography-tandem mass spectrometry conditions
[0069] The QA in the sample was quantitatively analyzed by liquid chromatography-tandem mass spectrometry (LC-MS / MS) technology. The specific detection conditions are as follows:
[0070] HPLC-MS / MS equipment: Ultimate 3000 liquid chromatograph and QTRAP 5500 mass spectrometer were used in series. Liquid chromatography operating conditions: 0.1% formic acid water (C) and acetonitrile (D) were used as mobile phases to chromatographically separate QA on a Waters XBridge BEH C18 column (100mm x 2.1mm, 2.5μm); gradient elution was performed, and the specific steps of gradient elution were as follows: 0-5.0min, acetonitrile concentration increased from 12.5% to 60%; 5.0-5.1min, acetonitrile concentration decreased from 60% to 12.5%; 5.1-8.0min, acetonitrile concentration was maintained at 12.5%. The flow rate was set to 0.3mL·min -1 ; The injection volume was 5 μL.
[0071] Mass spectrometry conditions: ion source: electrospray ionization (ESI) in positive ion mode; scan mode: multiple reaction monitoring (MRM); ion source temperature was 500°C; other parameters are shown in Table 1.
[0072] Table 1 Structures, physicochemical properties and MS parameters of five QAs.
[0073]
[0074] 4. Sample Collection and Pretreatment
[0075] The samples for this study included surface water, chicken, and fish. The surface water samples were collected from the Xiaoqing River in Jinan City, while the wastewater samples were taken from the inlet of the main wastewater treatment plant in the area. The collected water samples were filtered using a polyethersulfone membrane to remove impurities.
[0076] To extract the target compounds from chicken and fish samples, meat samples were purchased from a local supermarket. Subsequently, 1.0 g of meat sample was weighed and 3 mL of 2% formic acid-acetonitrile solution was used as the extraction solvent. The extraction process was carried out for 20 min using ultrasound-assisted extraction technology. After the extraction was completed, the resulting mixture was centrifuged to separate the supernatant. This extraction step was repeated twice to ensure sufficient extraction of the target compounds. The solutions obtained from the two extractions were combined and dried under a nitrogen flow to remove the solvent. The dried residue was then redissolved in pure water and the target compounds were further purified and enriched using solid phase extraction technology using CMP-I as the extraction medium.
[0077] 5. Solid Phase Extraction Process
[0078] The ground CMP-I material (40 mg) was filled into a 3 mL solid phase extraction column, and then 6 mL of methanol and 6 mL of deionized water were used at 1 mL min -1 Accurately draw 500mL of water sample and flow at 5mL min -1 After the sample was loaded onto the column, 6 mL of purified water was used to remove impurities and vacuum dried. Subsequently, 8 mL of methanol was used as the eluent at a flow rate of 1 mL min. -1 The target analytes enriched on the solid phase extraction column were eluted at a flow rate of . The collected eluate was dried under a nitrogen stream, then redissolved with 1 mL of methanol: water (1:1), and finally filtered through a 0.22 μm organic membrane into a 2 mL injection vial. The QA in the sample was quantitatively analyzed by liquid chromatography-tandem mass spectrometry (LC-MS / MS).
[0079] 6. Adsorption Experiment
[0080] Determination of adsorption equilibrium: Take 10 mL of QA solution of certain concentration (1, 5, 10, 20, 50, 100, 200, 300, 500 μg mL -1 ) were added to the sample bottle, and then 5 mg of CMP-I was added, and the mixture was shaken at a constant temperature (25-45°C) in a water bath constant temperature oscillator for 24 hours. The adsorbed solution was filtered through a needle filter and the equilibrium concentration of QA was determined by liquid chromatography. The equilibrium adsorption amount was calculated according to formula 1:
[0081]
[0082] In the formula, q e is the equilibrium adsorption amount of QA (mg·g -1 ), C0, C e are respectively expressed as the initial concentration and adsorption equilibrium concentration of QA in the sample solution (μg·mL-1 ), V is the volume of the sample solution (mL), and m is the mass of the dried CMP-I (mg).
[0083] Determination of adsorption kinetics: 5 mg CMP-I was added to 10 mL QA solution (10 μg mL -1 ) and placed in a water bath constant temperature oscillator at 35°C. At a certain time t, a certain amount of sample solution was taken and filtered through a needle filter, and the concentration of QA at time t was determined by liquid chromatography. The adsorption amount was calculated according to formula 2:
[0084]
[0085] In the formula, q t is the adsorption amount of QA at time t (mg·g -1 ), C0, C t represent the initial concentration of QA in the sample solution (μg·mL -1 ) and the concentration at time t (μg·mL -1 ), V (mL) is the volume of the sample solution, and m is the mass of the dried CMP-I (mg).
[0086] Results and Analysis
[0087] 1. Structural analysis of CMP-I
[0088] The surface morphology of the material was characterized and analyzed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 The SEM image shows the unique coral-like morphology of CMP, with its structural lines showing unrestrained stretching and free branching ( Figure 1 a); In contrast, after modification with iodomethane, the surface morphology of CMP-I is disturbed and reshaped by the adsorbed ions. Its lines are no longer light and stretched, but instead present a layered and encrypted feature, with more protrusions and depressions, causing the entire coral-like structure to become more dense ( Figure 1 b). TEM images further confirmed that CMP ( Figure 1 c) and CMP-I( Figure 1 d) coral-like morphology.
[0089] The material structure was further verified by Fourier transform infrared spectroscopy (FTIR). Figure 2 As shown in a, the -C≡CH group of TEPT and the C-Br group of DPDE are at 3240 cm -1 and 616cm -1In the spectra of CMP and CMP-I, the disappearance of the characteristic peak of the -C≡CH group and the C≡C stretching vibration peak (2223cm -1 ), which indicates that the Sonogashira-Hagihara cross-coupling reaction has been successfully achieved. In addition, at 1350-1600cm -1 The absorption bands observed in this region are mainly related to the stretching vibrations of benzene and pyrimidine rings.
[0090] In addition, through solid-state 13 The molecular structure was verified by C nuclear magnetic resonance spectroscopy. Figure 2 As shown in (b), compared with CMP, in the spectrum of CMP-I, the chemical shift peaks in the range of 30.1-54.3ppm were observed to be significantly enhanced, which was attributed to the role of methyl carbon in the CMP-I structure. As an important connecting part of the topological network, the alkynyl group showed significantly different chemical shifts between the two polymers. The internal alkyne of CMP has two obvious peaks (chemical shifts at 88.8ppm and 94.9ppm). On the other hand, the characteristic peaks of the internal alkyne of CMP-I at similar chemical shifts become less obvious, and the peak intensity near the chemical shift of 78.3ppm increases significantly. This phenomenon may be caused by the different types and numbers of asymmetric internal alkyne groups caused by the methylation of CMP-I. The resonance peak of 130ppm can be attributed to the aromatic carbon of the benzene ring. The characteristic signal of the pyrimidine ring was detected at about 158ppm.
[0091] N2 adsorption-desorption isotherm analysis revealed that the BET surface area of CMP was 182.2 m2 g -1 , while the specific surface area of CMP-I after methylation treatment decreased significantly to 34.3 m2·g -1 ( Figure 2 c), this phenomenon may be attributed to I - Further observation revealed that CMP-I exhibited a richer mesoporous structure than CMP, which undoubtedly had a positive effect on improving the elution efficiency of the target.
[0092] Thermogravimetric analysis (TGA) curves revealed that CMP-I exhibited poor thermal stability compared to CMP ( Figure 2 d) The poor thermal behavior of CMP-I can be attributed to its ionic framework structure. In the temperature range of 25-300 °C, its mass loss is about 20%, mainly due to the I - In contrast, CMP has good thermal stability below 300 °C and its mass loss is low, which is mainly due to the desorption process of adsorbed water molecules in the material.
[0093] 2. Optimization of solid phase extraction method for detecting quinolone antibiotics
[0094] (1) Selection of adsorption materials
[0095] This study first conducted an in-depth study on the performance of CMP and CMP-I in terms of QA extraction efficiency. During the experiment, the same solid phase extraction operation was performed on a specific concentration of QA using a CMP solid phase extraction column and a CMP-I solid phase extraction column. The experimental results showed that despite trying a variety of different types of eluents to elute CMP adsorbed with QA, the recovery rate of QA failed to achieve satisfactory results (0.02-25.3%, Figure 3 a). However, when methanol was used as the eluent to elute CMP-I adsorbed with QA, the recovery rate of QA was significantly improved (95.9%-110.7%, Figure 3 b) This phenomenon is mainly attributed to the difference in the pore structure between CMP and CMP-I. The rich micropore and mesoporous structure of CMP-I is more conducive to the elution of the target, thereby achieving the reusability of the material.
[0096] (2) Single factor optimization of solid phase extraction conditions
[0097] This study optimized seven key experimental parameters in solid phase extraction technology, including solution pH, amount of adsorbent, ionic strength, sample flow rate, sample volume, type and amount of eluent. The recovery rate of quinolone antibiotics under different optimized conditions was measured to evaluate the extraction efficiency of solid phase extraction, and finally the optimal experimental parameters were determined.
[0098] The pH value of the sample solution has a significant effect on the existence state of QA and the adsorption characteristics of the adsorbent. The pKa values of the five QAs involved in the study range from 4.04 to 8.75. When the pH value is lower than the pKa value of QA, QA exists in molecular form; conversely, when the pH value is higher than the pKa value, QA exists in ionic form. The zero potential point of CMP-I is 6.62, which indicates that below this pH value, the surface of the material has a positive charge, and above this pH value it has a negative charge. In this study, an in-depth discussion was conducted on the pH range of 2 to 10. Figure 4 As shown in (a), the recovery of QA was found to be relatively high in the pH range of 2 to 4. However, when the pH was greater than 6, the recovery of QA decreased with the increase of pH. This phenomenon was mainly due to the weakening of the cation-π and π-π interactions between CMP-I and QA when the pH was greater than 6.
[0099] In the solid phase extraction process, the amount of adsorbent material used is a key parameter that determines the extraction efficiency. This study investigated the effect of CMP-I at different doses (20, 30, 40, 50, and 60 mg) on the recovery of five QAs. Figure 4 As shown in (b), when the adsorbent dosage was 20 mg, the recovery rate of QA was relatively low, which may be attributed to the fact that the amount of adsorbent material was insufficient to completely adsorb QA in the sample. However, when the amount of adsorbent material added was increased from 40 mg to 60 mg, the recovery rate did not increase significantly, indicating that 40 mg of adsorbent material was sufficient to adsorb the target compound in the sample. Based on this, the dosage of adsorbent material in the solid phase extraction column was selected as 40 mg in subsequent experiments.
[0100] The sample flow rate directly affects the interaction time between the target compound and the solid phase extraction adsorbent. This study investigated the interaction time between the target compound and the solid phase extraction adsorbent at different upsampling flow rates (1, 2, 3, 4, and 5 mL min -1 ) on the extraction efficiency of five QAs. Figure 4 As shown in (c), when the upsampling flow rate is between 1 and 5 mL min -1 When the flow rate was within the range of 50%, the recoveries of the five QAs were all over 90%, and no significant difference was observed with the increase of flow rate. This indicates that the effect of upsampling flow rate on extraction efficiency is minimal. Therefore, in order to improve the experimental efficiency, this study selected 5 mL min -1 Flow rate.
[0101] In addition, this study also explored the effect of different sample volumes (100, 200, 300, 400 and 500 mL) on the extraction efficiency of five QAs. Figure 4 As shown in (d), when the sample volume increased from 100 mL to 500 mL, the extraction recoveries of the five QAs remained relatively stable. When the sample volume was large, CMP-I was still able to maintain high extraction efficiency for the five QAs in the sample solution, which highlights the excellent performance of CMP-I in efficient enrichment of QAs. Therefore, 500 mL can be selected as the loading volume for subsequent experiments.
[0102] In this study, NaCl sample solutions with different concentrations (0, 0.1, 0.2, 0.4 and 0.8 M) were prepared to investigate the effect of ionic strength on the extraction efficiency of QA. Figure 4 As shown in (e), within the range of ionic strength investigated, ionic strength has no significant effect on the adsorption process of QA. Therefore, in subsequent experiments, there is no need to adjust the ionic strength of the sample solution.
[0103] Based on this, this study explored the effect of different methanol dosages (2, 4, 6, 8, 10 mL) on the elution performance of QA. Figure 4As shown in (f), when the eluent volume was in the range of 2.0 to 8.0 mL, a positive correlation was observed between the recovery rate and the eluent volume. However, when the eluent volume was increased to 10 mL, the recovery rate of QA was not significantly improved. Therefore, in subsequent experiments, 8.0 mL was selected as the optimal elution volume.
[0104] 3. Adsorption studies
[0105] In order to gain a deeper understanding of the adsorption performance of CMP-I for QA, a series of comprehensive experiments were carried out in this study, covering adsorption kinetics, adsorption isotherms and adsorption thermodynamics.
[0106] First, the adsorption kinetics of QA on CMP-I was studied. The pseudo-first-order and pseudo-second-order kinetics equations were used to fit the kinetic adsorption data. The results are shown in Figure 5 and Table 2. It can be seen that the pseudo-second-order kinetic equation can better describe the adsorption behavior of QA on CMP-I (R 2 ≥0.9965).
[0107] In this study, the adsorption isotherms of QAs on CMP-I were investigated by mixing QAs solutions of different concentrations with 5 mg of CMP-I and shaking them evenly. The adsorption equilibrium data were fitted and analyzed using the Langmuir and Freundlich adsorption models. The Langmuir isotherm reveals the characteristics of monolayer adsorption and uniform distribution of adsorption sites, while the Freundlich isotherm is used to describe multilayer adsorption on heterogeneous surfaces and is also applicable to multilayer adsorption. Experimental data (see Table 3 and Figure 5 ) shows that the R of the Langmuir model 2 The value (0.98471-0.99166) is higher than the R of the Freundlich model. 2 This result shows that the Langmuir model is more suitable for describing the adsorption behavior of QA on CMP-I, and that the adsorption of QA on the CMP-I surface tends to be monolayer adsorption.
[0108] To explore the effect of temperature on adsorption performance, this study investigated the adsorption effect of CMP-I on QA sample solutions in the temperature range of 25 to 45 °C. The experimental data (see Table 4) revealed that the ΔG value decreased with increasing temperature in the temperature range of 298.15 to 318.15 K, indicating that the adsorption process of QAs on CMP-I was spontaneous. The ΔH values of the five QAs were all positive, indicating that the adsorption process was an endothermic reaction. The ΔS values ranged from 67.42 to 73.49 J / mol / K, indicating that the disorder of the solid-liquid interface increased during the adsorption process.
[0109] Table 2 Adsorption kinetic parameters of QAs on CMP-I
[0110]
[0111] Table 3 Langmuir and Freundlich fitting parameters for the adsorption of five QAs on CMP-I adsorbent
[0112]
[0113]
[0114] Table 4 Thermodynamic parameters of adsorption of five QAs on CMP-I at different temperatures
[0115]
[0116] 4. Reproducibility and reusability of CMP-I
[0117] In this study, the reproducibility of CMP-I was evaluated by comparing the adsorption performance of CMP-I (n=5) prepared from different batches. The same CMP-I solid phase extraction column was further tested for its reusability by conducting continuous adsorption-desorption experiments. The experimental results showed that different batches of CMP-I showed small differences in adsorption performance, indicating that CMP-I has good reproducibility; in addition, CMP-I can still maintain a high adsorption efficiency after 10 consecutive adsorption-desorption cycles, which proves that CMP-I has good reusability.
[0118] 5. Analytical performance of the developed method
[0119] In this study, a comprehensive practical evaluation of the constructed analytical method was conducted. The evaluation indicators included matrix effect (ME), linear range, regression equation, correlation coefficient (r), limit of detection (LOD), limit of quantification (LOQ) and precision. For detailed results, please see Tables 5 and 6. Experimental data showed that in a variety of matrices, the ME of QA was between -14.49 and 14.75. This result suggests that the influence of ME in the experimental analysis process is negligible. In addition, the results also confirm that CMP-I has excellent anti-interference ability in complex environments. Therefore, a satisfactory linear range (water sample: 0.5-200ng·L -1 ; Meat sample: ng·g -1), and the correlation coefficient r value was between 0.9908-0.9991. The LOD of surface water samples was 0.05 to 0.12 ng·L -1 , the LOD of wastewater samples was 0.02 to 0.12 ng·L -1 , the LOD of meat samples was 0.03 to 0.12 ng·g -1 The precision of this method ranged from 2.28% to 10.47%. In summary, the SPE-LC-MS / MS method based on CMP-I showed high sensitivity, wide linear range and high precision, and has significant application prospects in the QA quantitative analysis of complex samples.
[0120] 6. QA Analysis in Water and Meat Samples
[0121] In this study, the proposed analytical method was used to select samples from various matrices such as surface water, wastewater, and meat for analysis. The experimental results showed that no QA residues were detected in the selected samples. To ensure the accuracy of the method, spike recovery experiments were carried out on the selected samples. Table 7 shows the spike recovery data obtained at different spike concentrations. The results showed that satisfactory recoveries were obtained in surface water, wastewater, and meat samples (the water sample recovery ranged from 70.9% to 114.9%, and the meat sample recovery ranged from 72.9% to 111.1%), indicating that the method constructed in this study has excellent accuracy.
[0122] Table 5 Detection performance of SPE-LC-MS / MS based on CMP-I in water samples
[0123]
[0124]
[0125] Table 6 Detection performance of SPE-LC-MS / MS based on CMP-I in meat samples
[0126]
[0127] Table 7 Content of QA in actual samples and spiked recovery (n=3)
[0128]
[0129] At 5, 10, 100 ng·L -1 (a, b, c) and 1, 5, 50 ng·g -1 (d, e, f) QA content added. ND means not detected.
[0130] 7. Comparison with other research methods
[0131] This study systematically compared the proposed method for detecting QA in water and meat samples with the methods reported in the existing literature by comparing key indicators such as detection limit, adsorbent dosage, linear range and enrichment factors (EFs). As shown in Table 8, compared with other methods, this method can still achieve a satisfactory low detection limit and show excellent enrichment factors while using less adsorbent, which fully demonstrates the excellent adsorption performance of CMP-I adsorbent. Comprehensive analysis shows that the solid phase extraction-liquid chromatography-tandem mass spectrometry (SPE-LC-MS / MS) method based on CMP-I has the advantages of high efficiency, high accuracy and high sensitivity in detecting trace QA.
[0132] Table 8 Comparison of QA determination methods
[0133]
[0134] like Figure 7 As shown, the present invention synthesizes and prepares an ionic CMP-I through the Sonogashira-Hagihara cross-coupling reaction as a solid phase extraction adsorbent for extracting QA from water and meat samples. Ionic CMP-I has the advantages of simple synthesis and good reusability. In addition, a QA trace detection method is developed, using ionic CMP-I as a packaging material for a solid phase extraction column and LC-MS / MS as a detector. The results show that this method has high sensitivity and low detection limit, and can meet the requirements for the determination of trace QA in meat and water.
[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A cationic conjugated microporous polymer, characterized in that: The cationic conjugated microporous polymer is a methylated conjugated microporous polymer, and the conjugated microporous polymer is polymerized from two monomers: 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,5-dibromopyrimidine.
2. A method for preparing the cationic conjugated microporous polymer according to claim 1, characterized in that: The following steps are involved: (1) After mixing 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, 2,5-dibromopyrimidine and a catalyst, the mixture is added into a solvent for cross-coupling reaction to obtain a conjugated microporous polymer; (2) Adding a halogenated hydrocarbon solution to carry out a methylation reaction on the conjugated microporous polymer to obtain a cationic conjugated microporous polymer.
3. The method for preparing a cationic conjugated microporous polymer according to claim 2, characterized in that: In step (1), the molar ratio of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, 2,5-dibromopyrimidine and catalyst is 1:(1-3):(1-2); Preferably, the molar ratio of the 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, 2,5-dibromopyrimidine and the catalyst is 1:1.5:1.
3.
4. The method for preparing a cationic conjugated microporous polymer according to claim 2, characterized in that: In step (1), the catalyst is bistriphenylphosphine palladium dichloride, cuprous iodide and triphenylphosphine; The molar ratio of bistriphenylphosphine palladium dichloride, cuprous iodide and triphenylphosphine is 1:(3-6):(1-3); Preferably, the molar ratio of bistriphenylphosphine palladium dichloride, cuprous iodide and triphenylphosphine is 1:5.4:2.3; Or, the solvent is triethylamine and N,N'-dimethylformamide; the volume ratio of triethylamine to N,N'-dimethylformamide is 1:(1-3); Preferably, the volume ratio of triethylamine to N,N'-dimethylformamide is 1:
1.
5. The method for preparing a cationic conjugated microporous polymer according to claim 2, characterized in that: In step (1), the conditions of the cross-coupling reaction are: stirring at 80-100° C. for 10-12 h under an inert atmosphere, and then refluxing at 110-150° C. for 60-80 h; Preferably, the conditions of the cross-coupling reaction are: stirring at 90° C. for 12 h under nitrogen, and then refluxing at 120° C. for 72 h.
6. The method for preparing a cationic conjugated microporous polymer according to claim 2, characterized in that: In step (2), the mixing ratio of the conjugated microporous polymer and the halogenated hydrocarbon is (40-60) mg: 1 mL; Preferably, the mixing ratio of the conjugated microporous polymer to the halogenated hydrocarbon is 50 mg: 1 mL; The halogenated hydrocarbon solution is an acetonitrile solution of halogenated hydrocarbon; the volume fraction of the halogenated hydrocarbon is 0.1-0.2%; The halogenated hydrocarbon is methyl iodide or methyl bromide; Preferably, the halogenated hydrocarbon is methyl iodide; The conditions of the methylation reaction are: stirring the reaction at 60-80° C. for 30-40 hours; Preferably, the methylation reaction is carried out under stirring at 80° C. for 36 hours.
7. Use of the cationic conjugated microporous polymer according to claim 1 as a solid phase extraction adsorbent in enriching quinolone antibiotics, characterized in that: The quinolone antibiotics are norfloxacin, ciprofloxacin, enrofloxacin, gatifloxacin and ofloxacin.
8. A method for enriching quinolone antibiotics, characterized in that: The cationic conjugated microporous polymer according to claim 1 is fixed in a solid phase extraction column of a solid phase extraction device, solid phase extraction is performed to enrich the quinolone antibiotic residues in the sample, and the quinolone antibiotics in the sample are quantitatively analyzed by liquid chromatography-tandem mass spectrometry.
9. The method for enriching quinolone antibiotics according to claim 8, characterized in that: During the solid phase extraction process, the pH of the sample is 2-10; preferably, the pH of the sample is 2-4; The amount of the cationic conjugated microporous polymer added is 20-60 mg; preferably, the amount of the cationic conjugated microporous polymer added is 40 mg; Sampling flow rate is 1-5mL·min -1 ; Preferably, the sampling flow rate is 5mL·min -1 ; The sample volume is 100-500 mL; preferably, the sample volume is 500 mL; The eluent is ethyl acetate, 2,3-hexanedione, acetone, dichloromethane and methanol; preferably, the eluent is methanol; The volume of the eluent is 2-10 mL; preferably, the volume of the eluent is 8 mL.
10. The method for enriching quinolone antibiotics according to claim 8, characterized in that: The conditions of the liquid chromatography analysis are as follows: the chromatographic column used is a BEH C18 chromatographic column, the injection volume is 1-5 μL, and the flow rate is 0.1-0.5 mL·min -1 , the column temperature is 30-35°C; the mobile phases used include phase A and phase B, the phase A is 0.1% formic acid aqueous solution, the phase B is pure acetonitrile, and gradient elution is used; The procedure of the gradient elution is: 0 min, mobile phase A was 87.5%, mobile phase B was 12.5%; At 0-5 min, mobile phase A was reduced from 87.5% to 40%, and mobile phase B was increased from 12.5% to 60%; At 5-5.1 min, mobile phase A increased from 40% to 87.5%, and mobile phase B decreased from 60% to 12.5%; At 5.1-8 min, mobile phase A was 87.5% and mobile phase B was 12.5%; Preferably, the BEH C18 column is 100 mm x 2.1 mm, 2.5 μm; the injection volume is 3 μL, and the flow rate is 0.3 mL min -1 , column temperature was 35°C; Or, the conditions of the mass spectrometry analysis are: ion source: electrospray ionization in positive ion mode; scanning mode: Multiple reaction monitoring mode; ion source temperature was 500 °C.
Citation Information
Cited By
Enrichment material of estrogen substances and analysis method thereof
CN121338717A
An estrogen-like substance-enriched material and a method for analyzing the same
CN121338717B